Interactions between hyaluronic acid and CoCrMo alloy surface in simulated synovial fluids. Issue 4 (3rd October 2021) - Radice, Simona; Tibbits, Gretchen; Lin, Alex Y. W.; Beyenal, Haluk; Wimmer, Markus A.
Abstract: The performance of CoCrMo alloy in orthopaedic implants may be unfavourably affected by hyaluronic acid (HA) in synovial fluid. In this study, the authors aimed to understand the interactions between HA and CoCrMo using dedicated electrochemical experiments and surface analyses. A sequence of electrochemical measurements (open‐circuit potential, linear polarization resistance, potentiodynamic and potentiostatic polarizations) was run on LC‐CoCrMo (ASTM F1537) in Dulbecco's phosphate‐buffered saline (DPBS) solution with and without HA and in DPBS mixed with newborn calf serum (NCS) and HA, partially under simultaneous recording of surface pH using custom‐made microelectrodes. Samples were analysed by optical and electron microscopy. HA had no significant impact on the corrosion potential of CoCrMo alloy ( E CORR = −173 ± 8, −211 ± 16, and −254 ± 30 mVAg/AgCl, in DPBS, DPBS + HA, and DPBS + NCS + HA, respectively). Average current density values at the transpassive domain were double in DPBS compared to DPBS + HA and DPBS + NCS + HA. At potentials above +0.6 VAg/AgCl, surface pH values decreased from 7.5 to 6.5 in DPBS and from 7.5 to below 4 in DPBS + HA. In conclusion, the presence of HA did not compromise the corrosion resistance of CoCrMo alloy at free potential, but it enhanced acidic conditions at the near surface under anodic‐applied potential in the transpassive domain.